ChemInform Abstract: Orthorhombic In2O3: A Metastable Polymorph of Indium Sesquioxide. Issue 39 (5th September 2013) - Bekheet, Maged F.; Schwarz, Marcus R.; Lauterbach, Stefan; Kleebe, Hans‐Joachim; Kroll, Peter; Riedel, Ralf; Gurlo, Aleksander
Abstract Orthorhombic o′‐In2O3 (Rh2O3(II)‐type, space group Pbcn, Z = 4) is synthesized in macroscopic quantities (ca. 10—100 mm3) from rhombohedral corundum‐type rh‐In2O3 at 8—9 GPa and 600—1100 °C in multianvil and toroid cell assemblies.